INFLUENCE OF DEBT AND RISK MANAGEMENT SKILLS ON THE MANAGEMENT OF SMALL AND MEDIUM SCALE ENTERPRISES (SMEs) IN UMUAHIA METROPOLIS, ABIA STATE, NIGERIA - Emeasoba, Nneka Charity; Onyiorah, Blessing Onyeka; Eneogwe, Victoria Nwamara; VictorIgwe, Juliet Nkechi; Akpa, Chinenye Clara; Adieze, Charity; Akudolu, Chikerenma Adanma; Nwatarali, Chinwe Nene; Ndom-Uchendu, Maritha Nwakaego; Ikpeama, Frednora Uchenna; et al. (Veredas do Direito, 2026)
The study examined the influence of debt and risk management skills on the management of Small and Medium Scale Enterprises (SMEs) in Umuahia metropolis, Abia State. Two research questions and two hypotheses guided the study. The study adopted a descriptive survey research design. The entire population of 180 SME owners/managers in Umuahia metropolis, Abia State, Nigeria were used for the study. Therefore, census sampling technique was adopted because the entire population is manageable. The instrument for data collection was a 14-item structured questionnaire developed by the researcher, titled "Influence of Debt and Risk Management skills on management of Small and Medium Scale Enterprises Questionnaire (IDRMSMEQ). The designed instrument was validated by three experts in Business Education and Measurement and Evaluation. A reliability coefficient level of 0.80 was obtained. Data obtained were analyzed using descriptive statistics of mean for the research questions, standard deviation to determine the closeness and homogeneity of the responses and an independent t-test at a 0.05 level of significance to analyse the hypotheses. The findings revealed a high influence of debt and risk management skills on the management of Small and Medium Scale Enterprises (SMEs) in Umuahia metropolis, Abia State and that there was no significant difference in the debt and risk management skills of experienced and less experienced SME operators/managers. There is empirical evidence showing that debt and risk management skills have high influence on the management of Small and Medium Scale Enterprises (SMEs) in Umuahia metropolis, Abia State, there is need for proper awareness and implementation for a better management of Small and Medium Scale Enterprises (SMEs). Recommendations were made, one of which is that government agencies, financial institutions and educational bodies should organize continuous financial literacy training programmes for both experienced and less experienced SME operators to enhance effective financial decision making and sustainable business growth.